Nobility of spirit : a forgotten ideal - Riemen, Rob, 1962- (New Haven : Yale University Press, 2008)
In the pages of this slim, powerful book Rob Riemen argues with passion that "nobility of spirit" is the quintessence of a civilized world. It is, as Thomas Mann believed, the sole corrective for human history. Without nobility of spirit, culture vanishes.
Table of Contents -- Foreword by George Steiner -- Prelude: Dinner at the River CafÃ© -- The Quest of Thomas Mann -- Untimely Conversations on Timely Questions -- Be Brave -- Selected Bibliography -- Authorâ€?s Note
Includes bibliographical references (pages 113-114).
Print version record.
JSTOR
Keywords: Nobility of character; Noblesse de caractère.; PHILOSOPHY -- Social; PHILOSOPHY -- Ethics & Moral Philosophy; Nobility of character